Cryopreservation of rat spermatozoa: impact of freezing rate influenced by liquid nitrogen vapor phase cooling on post-thaw sperm motility - Fox, Katrina (Kansas State University, 2012)
Artificial insemination and cryopreservation of sperm are important components of any transgenic animal facility because they allow for the reduction in animal colony size and the safe storage of germplasm from valuable strains. In addition, they allow long-term storage of these strains and easy transportation of the genetic material to other research facilities internationally. Thus far, only one laboratory has created live rat pups after sperm cryopreservation and intrauterine insemination. Another laboratory made advances in cryopreservation media that improved sperm motility post-thawing, but no pups resulted from this work. In my study, these two cryopreservation media were utilized to perform intrauterine inseminations with both fresh samples of rat sperm as well as samples that were cryopreserved in liquid nitrogen to replicate and extend these studies. Pharmacoejaculation was tested as a means to obtain spermatozoa without euthanizing the male to collect the epididymis, but results were inconsistent and the samples were not useful for intrauterine inseminations or cryopreservation. Epidiymal sperm was then collected into the various media and frozen in liquid nitrogen. In my hands, the frozen/thawed rat sperm achieved motility of less than 1%. Next, the impact of altering the freezing rate on sperm motility was evaluated. Epididymal sperm was collected and processed using a modified protocol and were then frozen at 2, 4 or 6 cm above the level of liquid nitrogen. Four to six days after freezing, samples were thawed and post-thaw sperm motility was evaluated. Sperm motility was measured prior to freezing as well as after-thawing. The sperm motility was correlated with LIVE/DEAD® staining. Sperm motility did not differ between the groups as a result of the freezing rate (Friedman test p=0.23). The published techniques are not robust and require further development to improve the motility of rat sperm after cryopreservation and achieve pregnancy via intrauterine insemination.
Keywords: Rat; Spermatozoa; Cryopreservation; Veterinary Medicine (0778)